Answer :

ZJSG09112007

Answer:

[tex]-8r^9p^6m^3[/tex]

Step-by-step explanation:

[tex](-2r^3p^2m)^3\\\\\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^n=-a^n,\:\quad \mathrm{if\:}n\mathrm{\:is\:odd}\\\\\left(-2r^3p^2m\right)^3=-\left(2r^3p^2m\right)^3\\\\\mathrm{Apply\:exponent\:rule}:\quad \left(a\times\:b\right)^n=a^nb^n\\\\\left(2r^3p^2m\right)^3=2^3\left(r^3\right)^3\left(p^2\right)^3m^3\\\\=-2^3\left(r^3\right)^3\left(p^2\right)^3m^3\\\\2^3=8\\=-8\left(r^3\right)^3\left(p^2\right)^3m^3\\\\\mathrm{Simplify\:}\left(r^3\right)^3:\quad r^9\\\\=-8r^9\left(p^2\right)^3m^3[/tex]

[tex]\mathrm{Simplify\:}\left(p^2\right)^3:\quad p^6\\\\=-8r^9p^6m^3[/tex]

Other Questions